Analysis of the Spatio-Temporal Variability of Air Temperature Near the Ground Surface in the Central Baltic Area from 2005 to 2019 - Agu Eensaar (Atmosphere, 2020)
In this study, we analyzed the changes in the average daily, monthly, seasonal, and annual surface air temperatures based on the temperature data obtained from seven stations (1 January 2005–31 December 2019; 15 years) belonging to the central Baltic area (Stockholm, Tallinn, Helsinki, Narva, Pärnu, Tartu, and Võru). The statistical analysis revealed that there was a strong correlation between the daily average surface air temperature of the studied cities (range: 0.95–0.99). We analyzed the frequency distribution of the average surface air temperatures in addition to the Kruskal–Wallis and Dunn’s tests (significance level of 0.05) to demonstrate that the difference in air temperatures between Narva, Tallinn, Tartu, and Stockholm are critical. The Welch’s <semantics>t</semantics>-test (significance level 0.05), used to study the differences in the average monthly air temperature of the cities in question, showed that the surface air temperatures in Stockholm do not differ from Tallinn air temperatures from May to August. However, the surface air temperatures of Narva were similar to those of Tallinn in September. According to our results, the trends in the changes of monthly average surface air temperatures have a certain course during the year (ranging from 1.8 °C (Stockholm) to 4.5 °C (Võru and Tartu) per decade in February). During the entire study period, in addition to February, the surface air temperature increased in all the studied cities in March, May, June, and December, and the surface air temperature did not increase in January or from July to October. During the study period, the average annual surface air temperature in the cities of the central Baltic area increased by 0.43 °C per decade. The results also confirm that the surface air temperature in the study area is changing differently in different cities. The acceleration of the surface air temperature is very alarming and requires a significant intensification of the measures taken to slow down the temperature rise.